Gene mutations associated with fertilization failure after in vitro fertilization/intracytoplasmic sperm injection - Xue, Yamei; Cheng, Xiaohong; Xiong, Yuping; Li, Kun (Frontiers in Endocrinology, 2022)
Fertilization failure during assisted reproductive technologies (ART) is often unpredictable, as this failure is encountered only after in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) have been performed. The etiology of fertilization failure remains elusive. As high throughput sequencing techniques are becoming widely available, more and more mutations of genes are found to be involved in human fertilization failure in infertile patients. In this review, we outline the recently discovered gene mutations that can contribute to the fertilization failure of IVF/ICSI attempts. The mutations of nine important genes expressed in sperm or oocytes, PLCZ1, ACTL7A, ACTL9, DNAH17, WEE2, TUBB8, NLRP5, ZP2, and TLE6, were summarized. These abnormalities mainly have shown Mendelian patterns of inheritance, including dominant inheritance and recessive inheritance, although de novo mutations were present in some cases. In this review, we summarized the mutations of the corresponding genes and their phenotypes during fertilization. The mutations may become promising targets for precision treatments in reproductive medicine. This study will give useful and timely information on the genetic causes of infertility for patients, and provide some helpful clues for genetic counseling and optimizing the strategy for clinical treatments in the ART context.